Food pharmacy : a guide to gut bacteria, anti-inflammatory foods, and eating for health - Aurell, Lina Nertby; Clase, Mia (Skyhorse Publishing, 2017)
"Food Pharmacy tells the complete story of friendly bacteria, intestinal flora, anti-inflammatory superfoods like turmeric, the difference between good and bad fats, and how we can reduce inflammation and heal chronic diseases by regulating our immune system with the right natural foods. Marrying scientific research with seventeen supplementary recipes, practical advice, and a quirky voice, Food Pharmacy extols the kitchen's anti-inflammatory heroes--like avocado, cloves, kale, cinnamon, and green bananas--and shows you how to live your healthiest life equipped with the right knowledge and food"--Back cover.